Evaluating the accuracy of CAD/CAM optimized stones compared to conventional type IV stones - Ceylan, Gülsüm; Emir, Faruk (Public Library of Science, 2023)
This study compared the accuracy (trueness and precision) of stone models fabricated using two brands of CAD/CAM optimized stones Cerec Stone (BC) and Elite Master (EM), and a conventional type IV stone Elite Rock Fast (ERF). 30 conventional Type IV and scannable stone complete-arch models were scanned with a blue LED extraoral scanner, and root mean square values were obtained. 6 abutments were used in complete-arch models. The digital models were compared with the master model to evaluate their trueness using model superimposition with Geomagic software. Precision was determined for each case by superimposing combinations of the 10 datasets in each group. The point cloud density of each model was calculated with MeshLab software. Kruskal-Wallis and Mann-Whitney nonparametric tests were used for the statistical analysis. The trueness of the stone models was 96 ?m for the BC, 88.2 ?m for the EM, and 87.6 ?m for the ERF. There were no significant differences between the tested dental stones (p = .768). However, the EM models (35.6 ?m) were more precise than the BC (46.9 ?m) and ERF (56.4 ?m) models (p = .001, p < .001). EM models also showed the highest point cloud density. There were significant differences in point cloud density (p = .003). The EM models showed significant differences in precision but no significant differences in terms of trueness. Although EM was more precise and had the highest point cloud density, all models were within the clinically acceptable limit.
Keywords: Conventional Type IV Stones; CAD/CAM; Optimized Stones